The future of spacetime - Hawking, S. W., (Stephen W.) (New York : Norton, 2002)
Presents adaptations of five speeches given on the occasion of the sixtieth birthday of scientist Kip Thorne, in which leading physicists, including Thorne, Stephen Hawking, Igor Novikov, Timothy Ferris, and Alan Lightman discuss different aspects of the modern physics of space and time.
Includes bibliographical references and index.
Booklist.
Choice.
Adult
Keywords: Space and time; Space and time